High quantum yield of In‐based halide perovskites for white light emission and flexible x‐ray scintillators. Issue 2 (26th October 2022) - Liang, Dehai; Liu, Xiaohui; Luo, Binbin; Qian, Qingkai; Cai, Wensi; Zhao, Shuangyi; Chen, Jiangzhao; Zang, Zhigang
Abstract: In‐based halides always present low photoluminescence quantum yield (PLQY) because of poor absorption, limiting their potential applications in luminescence‐related fields. In this work, zero‐dimensional MA4 InCl7 [MA + : CH3 NH3 + ] halides with different Sb 3+ doping level are prepared through solvent evaporating method. The Sb 3+ ‐doped MA4 InCl7 shows a broadband yellow emission with full width at half‐maximum of 180 nm and a high PLQY of 84%. Such broadband emission originates from the self‐trapped excitons demonstrated by experimental results and theoretical calculations. Additionally, the Sb 3+ ‐doped MA4 InCl7 is further employed to fabricate white‐light‐emitting diodes, which possesses high color rendering index of 91 and excellent operating stability up to 400 h. Moreover, flexible Sb 3+ ‐doped MA4 InCl7 films are also prepared as x‐ray scintillators, exhibiting low detection limit of 63.3 nGyair /s and high spatial resolution of 10.0 lp/mm. Thus, this work provides guidance to design perovskite‐based devices with bright luminescence and x‐ray detection with excellent flexibility. Abstract : The Sb 3+ ‐doped MA4 InCl7 [MA + : CH3 NH3 + ] shows a broadband yellow emission with a full width at half‐maximum of 180 nm and a high PLQY of 84%, which facilitates the applications of white light emission and flexible x‐ray imaging.